2007
DOI: 10.1002/pd.1643
|View full text |Cite
|
Sign up to set email alerts
|

Nuchal translucency measurement and congenital heart defects: modest association in low‐risk pregnancies

Abstract: In pregnancies without known risk factors also, an increased NT is associated with major cardiac defects in the fetus and therefore represents an indication for specialized fetal echocardiography. However, this association is too weak to envisage a role for NT measurement as single screening strategy for the prenatal detection of cardiac defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 38 publications
5
32
0
2
Order By: Relevance
“…78,120,121 The likelihood of a fetus with normal karyotype having CHD once an increased NT is detected increases from 1% to ≈3% for NT above the 95th percentile and to ≈6% for NT at or above the 99th percentile. 78,79,[122][123][124] The risk for CHD rises exponentially with increasing NT measurement, 79,[122][123][124][125] with a risk estimated at 24% if NT is ≥6 mm 80 and >60% with a NT ≥8.5 mm. 79 Some centers advocate use of the 95th percentile cutoff for a specific crown-rump length to determine the NT value above which a fetal echocardiogram should be offered.…”
mentioning
confidence: 99%
“…78,120,121 The likelihood of a fetus with normal karyotype having CHD once an increased NT is detected increases from 1% to ≈3% for NT above the 95th percentile and to ≈6% for NT at or above the 99th percentile. 78,79,[122][123][124] The risk for CHD rises exponentially with increasing NT measurement, 79,[122][123][124][125] with a risk estimated at 24% if NT is ≥6 mm 80 and >60% with a NT ≥8.5 mm. 79 Some centers advocate use of the 95th percentile cutoff for a specific crown-rump length to determine the NT value above which a fetal echocardiogram should be offered.…”
mentioning
confidence: 99%
“…In a pooled analysis of data from four large centers the same author found that a NT ≥2.5 and ≥3.5 mm was found in 35.5 and 23%, respectively, of 397 euploid fetuses with major CHD (Makrydimas et al, 2005). Low detection rates for CHD (around 15%) are reported in studies where NT is measured in unselected or low-risk populations (Westin et al, 2006;Müller et al, 2007) and when fetuses with cystic hygromas are excluded (Simpson et al, 2007). However, two recent studies, a meta-analysis of four studies and a 10-year overview of the association between nuchal fluid accumulation and CHD diagnosed at referral centers, re-evaluated the role of NT measurement in screening for CHD (Wald et al, 2008;Vogel et al, 2009) and showed enhanced detection and improved neonatal outcome in duct dependent CHD, such as transposition of the great arteries (Wald et al, 2008).…”
Section: Congenital Heart Defectsmentioning
confidence: 99%
“…They found that at nuchal translucency of at least the 95 th centile, the sensitivity for detecting CHD was 14%. Mü ller et al [8] looked at 4876 euploid fetuses from the low-risk population and found that the sensitivity of nuchal translucency measurement at higher than the 95 th percentile for detecting CHD was only 8%.…”
Section: Anomaly Screening In the First Trimestermentioning
confidence: 97%